Management of acute diarrhea in adults in China: a cross-sectional survey - Hou Feng-Qin; Wang Yan; LI Jun; Wang Gui-Qiang; Liu Ying (BMC Public Health, 2013)
Abstract Background The aim of this study was to evaluate the management of acute adult diarrhea in China and assess adherence of clinical practice to national guidelines and 2012 World Gastroenterology Organization guidelines. Methods A cross-sectional survey was carried out among physicians in 20 hospitals in two different areas of China (Beijing, 10; Shaanxi province, 10). Summary statistics were calculated for the overall study group and for each region. Between-region differences were assessed with χ2 or t-tests. Results Data were collected for 800 patients (≥18 years; mean ± SD age 37.0 ± 16.3 years; 56.4% female). The mean ± SD time between diarrhea onset and visiting a diarrhea clinic was 2.4 ± 1.6 days; this interval was significantly shorter in Beijing than Shaanxi (2.0 ± 1.4 vs 2.8 ± 1.8 days, respectively; p < 0.001). Overall, 31.4% of patients self-medicated before visiting the clinic, most commonly with antibiotics. Routine stool examinations were ordered for 70.6% of patients, vibrio cholera stool culture for 57.5%, but non-vibrio bacteria stool culture for only 11.4%. Only 61.6% of patients received fluid and electrolyte therapy: 28.3% oral rehydration solution (ORS) and 33.4% intravenous fluids (even though only 13.8% needed). Antibiotics were the most common drugs (60.8%) and the most common antibiotics were fluoroquinolones, followed by aminoglycosides. Totally 51.3% of patients received irrational antibiotic treatment (unnecessary for 47.9%; indicated but not prescribed for 3.4%). After antibiotics, the most commonly prescribed drugs were dioctahedral smectite (59.3%); For Shaanxi compared with Beijing, less individuals received ORS (7.8% vs 48.5%,respectively; p < 0.001) and more received intravenous fluids (46.3% vs 20.5%, respectively; p < 0.001). Significantly more of the patients in Shaanxi province were administered antibiotics (64.5% vs 57%, respectively; p = 0.03), and more received intravenous antibiotics than Beijing (49.0% vs 27.0%, respectively; p < 0.001). Conclusions Adherence to both national guidelines and 2012 World Gastroenterology Organization guidelines for the management of acute diarrhea in adult was limited among tertiary hospital physicians. The findings suggest nationwide education and effective health policies are needed to improve medical practice and reduce the unnecessary burden on the healthcare system.